Sistem Pemilu Proporsional Terbuka Perspektif Siyasah Dusturiyah - Muhaki, Muhaki (Journal of Social Science and Economics, 2023)
Even though the proportional election system is open in a country where the majority of the population is Muslim, Islamic shari'at as the way of life of the majority population is never used to test its validity. Therefore, this research attempts to explain the problems of an open proportional election system based on the theory of fiqh siyasah dusturiyah as a representation of the manhaj of Indonesian Muslims. Problem focus: First, what is the concept of an open proportional election system in the components of the election system?; Second, what is the relevance of the open proportional election system according to the principle of the shura system? Third, what is the validity of the open proportional election system according to the legal view? The method used is normative juridical, namely a method that attempts to explain the rules of the system and their implications for various components of the election system. The first finding, an open proportional electoral system as a formula for converting people's votes into seats for state administrators. And candidates are proposed by political parties, but parties cannot determine the electability of their candidates. Second, according to the shura principle, an open proportional election system is relevant to be implemented as a principle for realizing public accountability in government. Third, the application of a proportional system with an open list is more in line with the principles of Islamic law, because it provides fair treatment to the aspirations of the people and encourages a pattern of mutually bound relationships between candidates and the people (voters) so as to bring them closer to each other. realization of public benefit. In conclusion, according to siya>sah dustu>riyah the open proportional election system does not conflict with the universal principles of Islamic shari>'at because it is more likely to have implications for the maintenance of maqas}id, namely hifz}'aql in the form of the rights to freedom of speech and choice. or elected by a majority of voters.